Pendampingan Inovasi Baru dalam Mempertahankan Produksi UMKM Gula Kelapa Sebagai Upaya Menjaga Eksistensi Ekonomi Rumah Tangga Pedesaan - Suci Larasati; M. Adib Fuadi Nuriz (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This assistance program aims to strengthen production resilience and maintain the existence of Mr. Syamsudin's coconut sugar MSME in Dayakan Hamlet, Wagir Lor Village, Ngebel Subdistrict, Ponorogo Regency. The method used is the Asset Based Community Development (ABCD) approach with observation, interviews, participatory discussions, and field documentation techniques. The results of the assistance show that this coconut sugar business, despite being managed traditionally with limited labor, has been able to survive for more than a decade as a pillar of the family's economy. The innovations offered, namely the use of ziplock plastic packaging with simple labels and the use of digital marketing through WhatsApp Business and social media, have proven to increase the attractiveness of the product and expand its market reach. This assistance not only supports the economic aspects of families but also contributes to the preservation of local traditions and the empowerment of rural communities. With more professional management and support from the village government, coconut sugar MSMEs have the potential to become leading village products that have both economic and cultural value.